OPTIMALISASI PEMANFAATAN SUMBER DAYA GENETIK PADI MELALUI VALUASI EKONOMI (Forum Penelitian Agro Ekonomi, 2024)
Indonesia has potency of widely diverse genetic resources of rice useful to assembly the new varieties. This study aimed to analyze (1) diversity of genetic resources and their utilization in the assembly of rice varieties; (2) importance of preserving the diversity of rice genetic resources; (3) a conceptual overview of economic valuation of genetic resources of rice; and (4) economic value of genetic resources of rice. This paper is a literature review related to genetic resources and economic valuation of rice. The results show that the economic valuation of genetic resources of rice necessary to do in order to become a reference for breeders of rice in assembling new varieties of rice in accordance with preferences of rice farmers and consumers, so that the new varieties of rice produced to be widely adopted and provide economic impact on communities. In addition, in the conditions of limited conservation budgets, economic valuation can be used to better focus efforts to manage genetic resources that are considered to provide greater economic benefits. The management of genetic resources could be done through exploration, conservation, characterization and evaluation, documentation, as well as the exchange of material and information between research institutions from home and abroad.